Feeding ecology of juvenile dog snapper Lutjanus jocu (Bloch and Shneider, 1801) (Lutjanidae) in intertidal mangrove creeks in Curuçá estuary (Northern Brazil) - MONTEIRO, Dijane Pantoja (2015)
The diet and feeding ecology of juvenile dog snapper (Lutjanus jocu) were investigated in 92 specimens collected in four intertidal mangrove creeks of Curuçá estuary, Northern Brazil, between September 2003 and July 2004. No significant differences in total length were found between the sampling months. Feeding intensity was high as indicated by high stomach fullness index and low vacuity index. The most important prey was Penaeidae, followed by Grapsidae and Porcellanidae. The diet of juvenile dog snapper showed clear seasonal differences. Specimens from dry season (September and November) and dry / wet season transition (January), were specialists feeding exclusively on Penaeidae. However, the specimens from wet season (March and May) and wet /dry season transition (July) that consumed mainly Grapsidae, Penaeidae and Porcellanidae were generalist. These seasonal changes in diet could be related to variations in food availability.